Psychological Well-Being as Correlate of Academic Achievement among Postgraduate Students in Ghanaian Public Universities - N-yelbi, John; Awuku-Larbi, Mary Magdalene (Journal of Education and Practice, 2024)
Purpose: The purpose of the study was to examine postgraduate students' psychological well-being as correlate of their academic achievement in Ghanaian public universities. Methodology: The study adopted a quantitative approach underpinned by a cross-section design. The population of the study comprised of postgraduate drawn from three public universities in Ghana. A sample of 140 students between the ages of 29 to 45 years were drawn using simple random sampling. Psychological well-being scale and academic achievement questionnaire were employed for data collection. Research hypotheses 1 and 2 were analysed using Pearson correlation and independent sample t-test. Findings: The study reported a strong positive correlation between the psychological well-being and academic achievement. The study further that reported gender differences exist in psychological well-being and academic achievement. Findings revealed a statistically significant correlation existed between psychological well-being and academic achievement. Also, the study reported a statistically significant gender difference in psychological well-being and academic achievement. Unique contribution to theory, policy and practice: The study recommends that counsellors and psychologists should integrate psychological well-being theory and academic achievement theory to explain how psychological well-being influence academic achievement. The study recommends that University in collaboration with counsellors and psychologists should institute psychological well-being focused initiatives such as mindfulness training, peer support groups, and counselling services into postgraduate programmes. Also, it was recommended that universities should institute peer mentoring initiatives where students will be paired with train mentors for support and guidance.